Strengthening the Philippine Education Sector Through Fiscal and Monetary Policies: Analyzing Government Interventions from a Public Sector Accounting Perspective - Hazel S. Osano; Christopher M. Villaronte; Anik Yuesti; Joel Arante Alve (Juara: Jurnal Riset Akuntansi, 2026)
Amid ongoing economic challenges, this paper analyzes how fiscal and monetary policies have influenced the resilience and growth of the Philippine education sector, with emphasis on public sector accounting perspectives related to budget accountability, transparency, and government expenditure effectiveness. Using a qualitative-descriptive approach based on secondary data, the study highlights that increased government spending helped sustain learning continuity, improve digital infrastructure, and support post-pandemic recovery. From an accounting perspective, education fund allocation and utilization require accountable reporting, performance-based budgeting, and evaluation of whether public expenditure produces measurable educational and social outcomes. These findings align with the Keynesian Intertemporal Synthesis (KIS-CES) model, which emphasizes the multiplier effects of public investment, particularly in education. Monetary policy also played an indirect role, as accommodative measures by the Bangko Sentral ng Pilipinas helped create a stable macroeconomic environment that supported education financing. However, inflation and reduced household purchasing power continue to affect access and equity. The study also supports Human Capital Theory and Endogenous Growth Theory, which view education as a driver of long-term development. Overall, the results affirm the need for sustained, inclusive, coordinated, and accountable policy actions.